2007
DOI: 10.1111/j.1365-2648.2007.04298.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to reducing the use of restraints in residential elder care facilities

Abstract: Further education and support for staff and family members in evidence-based practice in relation to resident care and restraint use is needed in at least some residential elder care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 21 publications
3
78
0
2
Order By: Relevance
“…Similarly Johnson, Ostaszkiewicz, and O'Connell, 2009 reported that the nurses initiated the use of restraints in all cases [44]. Moore and Haralambous indicated that restraints were sometimes applied for the convenience of nursing staff rather than for the safety of patients [19]. Our results indirectly corroborated this possibility.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly Johnson, Ostaszkiewicz, and O'Connell, 2009 reported that the nurses initiated the use of restraints in all cases [44]. Moore and Haralambous indicated that restraints were sometimes applied for the convenience of nursing staff rather than for the safety of patients [19]. Our results indirectly corroborated this possibility.…”
Section: Discussionsupporting
confidence: 82%
“…Although nurses are aware of the ethical dilemmas arising from the use of physical restraints and are uncomfortable with their decision to use them, they often feel that they have no alternatives if they are to keep the patient safe [47], or that it is easier to apply restraints than think of alternatives [19]. Nurses would benefit from exposure to technologies that could improve patient and caregiver safety [48].…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers to shortening the restraint use included: fear of patient injury, staff and resource restrictions, lack of education and information about alternatives to restraints, policy and management issues, beliefs and expectations (of staff, family and residents), inadequate review practices and statement barriers (Moore & Haralambous 2007).…”
Section: Barriers Hindering Restraint Eliminationmentioning
confidence: 99%
“…13 Various types of coercive measures, such as mechanical and non-mechanical restraint, compulsion to take part in nursing and medical treatments or activities of daily life (ADLs), seem to be common practice in institutional care in most Western countries. 7,[14][15][16][17][18][19] Coercive measures have been associated with severe adverse effects. 12,14,17,18 Despite coercive measures' harmful effect on quality of life, use of them is probably primarily based on lack of education and unawareness of alternative measures.…”
Section: Introductionmentioning
confidence: 99%